Effects of integrated plant nutrition systems with fertilizer deep placement on rice yields and nitrogen use efficiency under different irrigation regimes - Islam, S.M. Mofijul; Gaihre, Yam Kanta; Islam, Md. Rafiqul; Islam, Aminul; Singh, Upendra; Sander, Bjoern Ole (Elsevier, 2023)
Improved fertilizer management, with a combination of organic and inorganic inputs, has the potential to enhance rice yield while maintaining soil health. However, studies on the effects of broadcast prilled urea (PU) and urea deep placement (UDP) applied in combination with organic inputs (poultry litter [PL] and vermicompost [VC]), as integrated plant nutrition systems (IPNSs), on rice yields and nitrogen use efficiency (NUE) under alternate wetting and drying (AWD) irrigation are limited. We conducted field experiments during the dry and wet seasons of 2018, 2019, and 2020 to investigate the effects of fertilizer treatments, including control (no nitrogen), UDP, PU, and IPNSs (PU + VC, PU + PL, and UDP + PL) on rice yield and NUE under two irrigation regimes – AWD and continuous flooding (CF). The results revealed that fertilizer treatment and irrigation regime had significant (p < 0.05) interaction effects on rice yield and the agronomic efficiency of N (AEN) during the dry season. UDP significantly (p < 0.05) boosted rice yield, total dry matter (TDM), and NUE as compared to broadcast PU in both wet and dry seasons. Similarly, the IPNS treatment of UDP with PL significantly (p < 0.05) boosted rice yield, TDM, and NUE in comparison to broadcast PU. Under AWD irrigation, UDP alone produced higher rice yields than other treatments, while UDP, and UDP with PL produced similar yields under CF irrigation. During the dry season, AWD irrigation significantly (p < 0.05) increased rice yield, TDM, and AEN when compared to CF conditions, but during the wet season, AWD irrigation demonstrated a rice yield and NUE equivalent to CF. This research implies that using a UDP alone or in combination with PL as an IPNS could be a good way to boost crop productivity while also maintaining soil fertility.